Design e ética : sobre a proposição de um dispositivo pluriético - Cornélio, Henrique Friedrichs (Universidade do Vale do Rio dos Sinos, 2018)
The objective of this research is: to reflect on ethical principles pertinent to design, to propose a dispositif that contributes to the materialization of ethics. Firstly, it’s intend to present and discuss the positioning of the area (Design) regarding ethics from authors such as: Findeli, d'Anjou, Manzini and Verbeek, among other authors. In relation to the proposition of the principles, the instruments of orientation used were the works of Spinoza, Foucault, Morin and Singer contributing to the delineation of a pluri-ethics - understood as pertinent to the Design. Such instruments were operated methodologically through a bibliographical review (basic research modality), guided by the critical-reflexive character of metadesign - it is worth saying "philosophical". The discussion in four chapters ("On design and ethics", "From the proposition of a pluri-ethical basis", and "On the metaproject: device for the proposition of devices") aims to present, in the fourth chapter pluri-ethical to autopoietic "), aspects of a device that contributes to reflections on contemporary problems, attentive to the materialization of ethics.
Keywords: Design; Ética; Dispositivo; Metaprojeto; Design; Ethics; Dispositif; Metadesign; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial